2014
DOI: 10.1007/s10745-014-9704-2
|View full text |Cite
|
Sign up to set email alerts
|

Local Ecosystem Service Use and Assessment Vary with Socio-ecological Conditions: A Case of Native Coffee-Forests in Southwestern Ethiopia

Abstract: Ecosystem-based management requires the promotion and integration of locally relevant ecosystem services. This needs an understanding of which ecosystem services local people value and how local valuation varies with socio-cultural and market factors. We convened ten focus group discussions and performed 105 household surveys from major indigenous groups and recent settlers about local values of various forest-based ecosystem services in changing landscapes of southwest Ethiopia. We found that the extent of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 39 publications
(46 reference statements)
4
25
0
1
Order By: Relevance
“…Through direct local community involvement on our ES assessment process, we found out that a number of ES underpin food security, employment, and sociological benefits, even though, most commonly recognized provisioning services related to basic needs and immediate benefits, especially those that generate income. This result is reflected by other studies of landscapes undergoing transformation (Akwetaireho and Getzner, 2010;Tadesse et al, 2014;Bhatta et al, 2016;Sinare et al, 2016;Mensah et al, 2017). In our oil palm landscapes, ES remained important to local communities for at least one decade following the expansion of oil palm in the region.…”
Section: Discussion Common Agreed Upon Es To Manage the Oil Palm Lansupporting
confidence: 73%
See 1 more Smart Citation
“…Through direct local community involvement on our ES assessment process, we found out that a number of ES underpin food security, employment, and sociological benefits, even though, most commonly recognized provisioning services related to basic needs and immediate benefits, especially those that generate income. This result is reflected by other studies of landscapes undergoing transformation (Akwetaireho and Getzner, 2010;Tadesse et al, 2014;Bhatta et al, 2016;Sinare et al, 2016;Mensah et al, 2017). In our oil palm landscapes, ES remained important to local communities for at least one decade following the expansion of oil palm in the region.…”
Section: Discussion Common Agreed Upon Es To Manage the Oil Palm Lansupporting
confidence: 73%
“…Direct community involvement in ecosystem service research can contribute to improved natural resource management by acknowledging and responding to locally perceived tradeoffs (Tadesse et al, 2014). The direct involvement of local communities in research can also promote local engagement in finding solutions to ecosystem management challenges (Menzel and Teng, 2010;Meijaard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Men were more likely to have a higher awareness or perceived a higher value for firewood, charcoal and timber for profit-earning purposes (Martin-Lopez et al, 2012;Mensah et al, 2017). However, women demonstrated a higher knowledge of and more direct use of domestic fuel supply (Hamann et al, 2015;Juma, 1998;Tadesse et al, 2014). Women usually have a higher dependency on this ecosystem service (Mutandwa and Kanyarukiga, 2016), but under stress and shock conditions (e.g.…”
Section: Provisioningmentioning
confidence: 99%
“…Nevertheless, both of these studies concluded that women saw greater value or appreciated this type of ecosystem service more than men (Jefferson et al, 2014; Sang et al, 2016). (Kalaba et al, 2013a,b;Martin-Lopez et al, 2012;Mensah et al, 2017;Mutandwa and Kanyarukiga, 2016) But in some cases (Hamann et al, 2015;Juma 1998;Tadesse et al, 2014;Paudyal et al, 2015), women had more knowledge on domestic fuel supply…”
Section: Culturalmentioning
confidence: 99%
“…It is one of the most species-rich ecosystems that significantly contribute to the economic development of Ethiopia and is recognized globally as priority areas for the conservation of biodiversity [53]. However, supporting ecosystem services have been diminished because of deforestation, immigration, population growth, expansion of invasive species, expansion of agriculture, cultural transformation, and the lack of land ownership [54,55]. These threats result in the degradation of the habitat and biodiversity [56] in the investigated watershed.…”
mentioning
confidence: 99%